Ethical aspects of Dhaka University Tele-medicine System (Bangladesh Journal of Bioethics, 2015)
To provide basic health care services in rural areas is one of the major challenges for developing countries like Bangladesh because of lack of infrastructures and unavailability of qualified medical doctors in the villages. Telemedicine viewed as a new way of offering health care services that has the potential to overcome this problem. Author is a member of extended group at Dhaka University (DU) which has been developing telemedicine equipment and data acquisition software to promote telemedicine practice in Bangladesh. PC based ECG equipment, Digital stethoscope, Digital microscope, Digital X-ray view box and some other essential medical equipment was developed for telemedicine services. The data acquisition software establishes an easy and appropriate patients to doctor interaction through a trained operator in a remote center that involve management and arrangement of consultation of a chosen and agreeing doctor by a patient. Upon establishing audio-visual connection between patient and doctor relevant physiological data from different diagnostic instruments will be uploaded securely in a dedicated web server which can be viewed real time using unique patient/doctor ID and password. Recently the Telemedicine group of DU and a local NGO named SAMAMA with support from Service innovation fund (SIF) of Prime Minister Office (PMO) of Bangladesh took the initiative to establish eight rural telemedicine centers and one expert center for the field trial of telemedicine in Bangladesh. The aim of this paper is to examine the ethical challenges of such health care system and our effort to overcome those problem before starting the field trial.